François Mauriac : the making of an intellectual - Welch, Edward, 1973- (Faux titre, 2006)
While François Mauriac's reputation as a novelist is well established, it is often forgotten that fiction forms only part of his output, and that in the post-war years especially, it was principally his activities as a journalist which kept him in the public eye. His interventions in the key debates of the period helped to consolidate his position as a major intellectual alongside Jean-Paul Sartre and Albert Camus. This book examines the evolution of François Mauriac's career during the twentieth century, and his gradual transformation from novelist to intellectual. Situating Mauriac and his ac.